Land and Fragility of Peace in Postwar Liberia: Concessions and Conflicts in the Midst of Poverty - Kepe, Thembela; Suah, Nyanquoi (Journal of peacebuilding & development, 2021)
On June 7, 2019, crowds of about 10, 000 people filled the streets of Monrovia, the capital city of Liberia, to protest against alleged corruption, injustice, and other failures of the government (Agence France-Presse News, 2019). These protests struck fear among Liberians, who had seen about 2 decades of civil war during the 1990s and early 2000s that left hundreds of thousands of people dead, million others internally displaced or exiled into neighbouring countries, infrastructure destroyed, and the quality of life severely diminished. While Liberia has now experienced relative peace since 2006, the two civil wars (1989–1997 and 1999–2003) are a reminder of what unresolved conflicts can do to peace in a nation. A general perception by Liberians is that discontent about the struggling economy, and the unresolved tensions around land and natural resource issues, among other things, could trigger another violent conflict if something is not done to address the status quo. The discontent about land historically goes hand in hand with the general perception among Liberians that through land-grabbing, as part of concessions awarded by the state, foreign companies enjoy stronger and more secured rights to land than local people (Gilfoy, 2015). Countrywide protests and riots by rural people in defence of their land rights that are threatened by land concessions to foreign companies clearly put land among the top possible triggers of another violent conflict such as seen during the civil wars. In Grand Bassa County, violent clashes between local people and security forces over palm plantation land “brought back memories of the nightmarish lawlessness of the war” (Jerving, 2015, p. 1). Similarly, in Butaw District, riots and suppression by security forces occurred at the Golden Veroleum Liberia oil palm plantation, leading the youth of the area to threaten “consequences” if the land issue was not resolved (Stokes, 2015). These, and many other examples, make the resolution of the land issue a crucial governance priority for the state. Beevers (2015) and De Simone (2015) see land and natural resource governance as central to peacebuilding, precisely because it is assumed that governance will address (land) injustices peacefully. In this briefing, we explore land conflicts as a threat to peace in Liberia. In particular, we reflect on the increasing tensions between local people in or near land concessions awarded to foreign companies by the state. We seek to understand how local people and the NGOs supporting them respond to conflicts created by overlapping land rights between the rural people and the foreign investors. This briefing seeks to highlight that land conflicts are no different from conflicts over minerals that are common triggers for violent conflicts in Africa and beyond. Our reflections are based on interviews we carried out in June 2019 in Monrovia, with the Liberian Land Authority, the National Bureau of Concession, and NGO representatives as well as with local people in the rural town of Gbah in Bomi County, whose land is being encroached upon by foreign companies who have legal concessions from the state. Gbah was chosen through convenience sampling, based on referrals from key informants dealing with land conflicts, as a community that exemplifies the land conflict between local people and a foreign company’s concession allocation. Following this introduction, the article provides a brief historical overview of the tensions over land as well as land policy and legislation, including the 2018 Land Rights Act (Republic of Liberia, 2018). This is followed by a discussion on how land concessions have exacerbated discontent over land, mainly as a result of land governance by the state. The concluding section reflects on the importance of good governance as an essential part of peacebuilding.